Comparison between flexible ureteroscopy in pre-stented group of patients and none pre-stented patients - Allahyani, Hossam; Alhayek, Rafe; Akhtar, Zeeshan (International journal of health sciences, 2024)
Background: Ureteroscopy has a low re-treatment rate and a high stone-free rate, making it a very successful therapy for ureteral stones. Though ureteral stent installation may make ureteroscope and ureteral access sheath insertion easier, it may come with more complications before and after the procedure. Aim: The objective of the research was to examine the disparities between pre-stenting and non-presenting ureteroscopy in the management of ureteral stones. Summary: Preoperative implantation of a ureteral stent may somewhat reduce the duration of surgery and enhance the stone-free rates in individuals having flexible ureteroscopy (fURS), however the effect is not statistically significant. Preoperative stenting resulted in a longer hospital stay and higher hospital expenses, but did not affect the incidence of complications and re-operations. Based on these data, it may be concluded that it is not justifiable to perform preoperative ureteral stent implantation before fURS for the treatment of upper urinary calculi. Nevertheless, due to the constraints of our study, more rigorous research, such as prospective randomized clinical trials, is necessary to validate our results.